Colour and textural typologies of goat cream butter with sea buckthorn (Hippophae rhamnoides L.) puree instrumental, sensory, and consumer input for product development - Chudy, Sylwia; Cais-Sokolińska, Dorota; Teichert, Joanna; Bielska, Paulina; Kaczyński, Łukasz K.; Biegalski, Jakub (2021)
In this research the effect of the addition of sea buckthorn puree (Hippophae rhamnoides L.) to goat cream butter was examined via analysis of its textural, physicochemical and sensory properties. Consumer acceptance was assessed. The addition of sea buckthorn promoted a stickiness and acidic flavour compared to the original goat butter. The number of consumers who liked goat butter increased by 35 %. The optimal amount of sea buckthorn added was determined as 1.5 %. A larger amount had a negative effect on the colour, as well as creating a more acidic flavour and fruit aroma.
U ovom radu je ispitivan dodatak pirea pasjeg trna (Hippophae rhamnoides L.) maslacu od kozjeg mlijeka pri čemu su određivani parametri teksture, fizikalno-kemijska i senzorska svojstva maslaca. Također, ispitivana je i prihvatljivost od strane potrošača. Dodatak pasjeg trna povećao je ljepljivost i aromu kiselosti u usporedbi s originalnim kozjim maslacem. Udio potrošača kojima se sviđao tako obogaćen maslac od kozjeg mlijeka narastao je za 35 %. Pokazalo se da je optimalna količina dodatka pasjeg trna 1,5 %. Veće količine dodatka utjecale su negativno na boju te na nastanak izraženijeg kiselog okusa i voćne arome.
Bibliografija: 41 jed.
Abstract ; Sažetak.
Keywords: Mliječni proizvodi -- Kozje mlijeko -- Maslac -- Pasji trn